2001
DOI: 10.1021/la010431a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Studies of Surface-Modified Glass Bead/Nafion Composites

Abstract: In the past decade, electrochemists have begun modifying electrode surfaces with polymer composites. Each of those composites had advantages over the standard polymer modified electrode. Usually, the major advantage is increased sensitivity. However, years of chromatographic research have proven that tailoring the surface of glass beads can increase the selectivity of a system. The same principle should be applicable to polymer film composites. This research is based upon making glass bead/ion exchange polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…This is consistent with previous experiments on glass bead/Nafion composites, which showed that there was no measurable effect on the electrochemical flux of Fe 3+ due to the formation of any of the glass bead/Nafion composites. 11 This similarity is expected because Fe 3+ is a small, hydrophilic inorganic ion which diffuses through both PSS and Nafion (D app ) 2.9 × 10 -7 cm 2 /s 22 ) rapidly, so small changes in the interfacial region have little effect on the electrochemical flux.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…This is consistent with previous experiments on glass bead/Nafion composites, which showed that there was no measurable effect on the electrochemical flux of Fe 3+ due to the formation of any of the glass bead/Nafion composites. 11 This similarity is expected because Fe 3+ is a small, hydrophilic inorganic ion which diffuses through both PSS and Nafion (D app ) 2.9 × 10 -7 cm 2 /s 22 ) rapidly, so small changes in the interfacial region have little effect on the electrochemical flux.…”
Section: Resultsmentioning
confidence: 93%
“…Earlier work in organosilane-modified glass bead/Nafion composites showed that the selectivity of the electrode could be altered by changing the functional end group on the organosilane. 11 This work examines the selectivity of organosilane-modified glass microsphere/PVP and PSS composites and the role of the polymer in the formation of these unique interfaces. Electrochemical selectivity is more complicated than chromatographic selectivity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations